2018
DOI: 10.3389/fimmu.2018.01913
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-Induced Human IL-10+ B Cells Do Not Show a Subset-Defining Marker Signature and Plastically Co-express IL-10 With Pro-Inflammatory Cytokines

Abstract: Regulatory B cells (Breg) have been described as a specific immunological subsets in several mouse models. Identification of a human counterpart has remained troublesome, because unique plasma membrane markers or a defining transcription factor have not been identified. Consequently, human Bregs are still primarily defined by production of IL-10. In this study, we sought to elucidate if in vitro-induced human IL-10 producing B cells are a dedicated immunological subset. Using deep immune profiling by multicolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
5
36
0
Order By: Relevance
“…Since our data show that B cell subsets are represented differently in blood and GALT, we wondered whether those B cells might be capable of producing cytokines such as TNFα and IL-10 ( 34 ). We analyzed B cells isolated from blood and two GALT sites: the Peyer's patches in the terminal ileum and colonic follicles in the rectum from the same donors for their production of intracellular TNFα and IL10 ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since our data show that B cell subsets are represented differently in blood and GALT, we wondered whether those B cells might be capable of producing cytokines such as TNFα and IL-10 ( 34 ). We analyzed B cells isolated from blood and two GALT sites: the Peyer's patches in the terminal ileum and colonic follicles in the rectum from the same donors for their production of intracellular TNFα and IL10 ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…CSA-Flow can be seamlessly integrated into multi-parametric FACS panels as part of complex cell-sorting strategies 44 , 47 , as the anti-cytokine antibodies can be pre-mixed with other cell surface antibodies and simultaneously applied to cells. Prior work with CSA has included pre-enrichment of cytokine-secreting immune cells using magnetic-based isolation 34 , 48 , 49 which can facilitate the subsequent study of particularly rare populations, and additional applications have included studies of cytokine detection kinetics 42 , cellular plasticity of cytokine expression 43 , 50 and interrogation of antigen-specific cytokine-expressing cells 34 , 49 . We envision that CSA-Flow can also be integrated in the workflow for next-generation and single-cell technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, a characterization of CpG-stimulated human B cells found that most IL-10 + B cells co-express TNF and IL-6 across a broad range of phenotypes. When purified, IL-10 + B cells were re-stimulated, their capacity to produce IL-10 was lost, while IL-10 − B cells were able to secrete IL-10 after a second challenge, arguing against the existence of a dedicated Breg lineage ( 18 ). IL-10 + Bregs can also be generated induced by anti-inflammatory factors, such as IL-35 and retinoic acid ( 89 , 90 ); whether these Bregs are more stable remains unclear.…”
Section: Breg Differentiation: Nurture or Nature?mentioning
confidence: 99%